ХX ÁSIR BASÍNDAǴÍ POEZIYADA MILLIY AǴARTÍWSHÍLÍQ MÁSELELERI - Davletov, B.A. (SCIENCE and SOCIETY, 2022)
The article deals with the study of the work of the son of Qazi Mavlik (Maudit) Bekmuhammed, his educational, cultural and enlightenment work. The ideological theme and genre features of the poet's lyrical songs are studied in detail. The author's contribution to translation studies is also discussed.